APOE ε4 influences β‐amyloid deposition in primary progressive aphasia and speech apraxia. Issue 6 (28th June 2014) - Josephs, Keith A.; Duffy, Joseph R.; Strand, Edythe A.; Machulda, Mary M.; Senjem, Matthew L.; Lowe, Val J.; Jack, Clifford R.; Whitwell, Jennifer L.
Abstract: Background: Apolipoprotein E ε4 ( APOE ε4) is a risk factor for β‐amyloid deposition in Alzheimer's disease dementia. Its influence on β‐amyloid deposition in speech and language disorders, including primary progressive aphasia (PPA), is unclear. Methods: One hundred thirty subjects with PPA or progressive speech apraxia underwent APOE genotyping and Pittsburgh compound B (PiB) PET scanning. The relationship between APOE ε4 and PiB status, as well as severity and regional distribution of PiB, was assessed. Results: Forty‐five subjects had an APOE ε4 allele and 60 subjects were PiB‐positive. The odds ratio for a subject with APOE ε4 being PiB‐positive compared with a subject without APOE ε4 being PiB‐positive was 10.2 (95% confidence interval, 4.4–25.5; P < .0001). The APOE ε4 allele did not influence regional PiB distribution or severity. Conclusion: APOE ε4 increases the risk of β‐amyloid deposition in PPA and progressive speech apraxia but does not influence regional β‐amyloid distribution or severity.